Feasibility study on three furfurylated non-durable tropical wood species evaluated for resistance to brown, white and soft rot fungi - Venås, Thomas Mark; Wong, Andrew H.H (IRGWP, 2008)
Furfurylation can protect non-durable wood species against biological degradation, but the method used today cannot fully protect the heartwood of Scots pine due to insufficient penetration. In order to test alternative wood substrates for furfurylation, three Malaysian grown wood species (Kelempayan, Rubberwood and Sena) were furfurylated and subjected to soil block decay testing. Their performance was compared to furfurylated Scots pine and furfurylated Beech modified using the same process. In addition, treatment characteristics were evaluated. One of the species tested, Kelempayan, seems to be a promising substrate for furfurylation. Kelempayan is easy to impregnate in both sap- and heartwood, and a 50% higher weight gain was reached using equivalent amounts of impregnation solution compared to Scots pine. Sena, Rubberwood and Beech returned weight gains 40-60% lower than Scots pine. Decay protection was largely comparable at equivalent weight percent gains for all wood species tested, although differences appeared. Generally, a weight gain of approximately 25% by furfurylation seems to offer good protection in the chosen soil block test.